A influência do grau de legibilidade e do gerenciamento de resultados no mispricing de ativos brasileiros - Mendes, Matheus Soares (2021)
The research had as main objective to evaluate to what extent of Readability and Earnings Management, are presented as determining factors for the presence of mispricing of shares in the Brazilian stock market, seeking theoretical support in the Theory of Disclosure and in Theory of Efficient Markets. Therefore, financial data and quarterly earnings releases for the period from 2011 to 2019 were used, captured in the Economatica and Thomson Reuters databases, as well as in the firms' IR sites. In order to meet the general and specific objectives, seven econometric models were developed, of which five were estimated by systemic GMM (Blundell & Bond, 1998), for offering robustness in terms of endogeneity, a common topic in accounting research (Barros et al., 2020). The other two, referring to the secondary model, were estimated using data from the Fixed Effects panel, according to previous research. Readability was estimated according to the study by Li, (2008) and corresponds to the fog index and the extent of the reports. The GR was estimated by the discretionary accruals, modeled by the model of Pae (2005). Among the main results, it stands out that, either individually or together, both Readability (negatively) and Earning Management (positively) presented themselves as determining factors for the calculation of pricing error of Brazilian assets. The sensitivity tests used in the research, using alternative proxies for the main study variables, confirm the findings and reinforce the inferences made. However, in a second moment, the research aimed to also analyze the relationship between the Readbility of the reports and the Earnings Management practices. In general, contrary to expectations, the discretionary accruals index is negatively related to readability. This finding reinforces the premise raised by Black et al. (2017), of an alternation in discretionary management practices to manage investor perceptions. Finally, the study aims to contribute to the knowledge of accounting science, with regard to the determinants of mispricing, filling some gaps in the subject and adding results to the existing literature.